COMPARISON OF SELECTED ANTHROPOMETRICAL AND PHYSICAL VARIABLES OF UNIVERSITY LEVEL KABADDI PLAYERS - Kumar, Dr Naresh (Innovative Research Thoughts, 2017)
Kabaddi is a combat sport that also involves physical contact. It is played between two teams, each of which consists of seven players, on a short, flat arena that is 10 metres by 13 metres (male) in size and is separated along the middle by a midline. The men's portion of the game lasts for a total of forty minutes (men's), which is broken up into two halves with a five-minute break in between each one. The game can be broken down into two distinct categories: offence and defence. Raider (the attacker) shall enter the opponent's court by continually repeating the word "Kabaddi"; and attempts to score points by using nis —lb to touch the opponents, or attempts to cross the bonus line. Raider may also attempt to score points by touching the opponents with their own hands. The kabaddi players were selected for the study using a systematic random sample method from the many kabaddi competitions held at the inter-zonal and zonal level.